GEOPHYSICAL INVESTIGATION OF GROUNDWATER CONTAMINATION USING DC RESISTIVITY TECHNIQUE AT THE MALE HOSTEL OF ISA KAITA COLLEGE OF EDUCATION DUTSIN-MA, KATSINA STATE, NIGERIA - Akpaneno, Aniefiok; Abdulwahab, S. (FUDMA JOURNAL OF SCIENCES, 2021)
A geophysical investigation involving Vertical Electrical Sounding (VES) using the Schlumberger array was carried out at the Isa Kaita College of Education specifically at the Male Hostel. The aim of the investigation is to explore the groundwater contamination of the area with the objectives: to determine the depth to basement of the study area, to determine the aquifer thickness, to determine the depth to aquifer, to determine the conductivity of the aquifer and to determine the thickness of topsoil and its variation in resistivity. A total of four (4) vertical electrical soundings were carried out using Schlumberger configuration. Terrameter signal averaging system (SAS) model 300 was the instrument used. The survey area is dominated by mainly four layers, namely: Topsoil, Weathered basement, fractured basement. The value of VES 03 and VES 04 have high electrical conductivities which likely shows they are contaminated, The topsoil resistivity along the profile ranges from approximately 1 to 154, The depth to basement (basement topography) Varies from 4.94 m to 7.59 m, The thickness of aquifer range from 1 m to 6.8 m. Therefore VES 02 has high Potential for groundwater because it has retaining capacity and good aquifer thickness and is therefore recommended for borehole establishment. It is recommended that the management of Isa Kaita College of Education should provide a concrete dumping site to avoid leaching of waste in ground thereby contaminating the groundwater.